A gender-based approach to the influence of personality traits on entrepreneurial intention - Laouiti, Rahma (2022)
While previous studies have demonstrated the importance of personality traits in the decision to pursue a career in entrepreneurship, more empirical evidence is needed to explain the mechanism through which entrepreneurial intention (EI) is strengthened. Accordingly, espousing a gender-based perspective, the current paper identifies characteristics that positively affect EI in a sample of 531 students in France. A fuzzy-set qualitative comparative analysis is performed yielding four alternate combinations that are likely to lead to high EI, of which two are gender specific. The inherent findings advance previous studies by offering entrepreneurship educators in France and similar contexts a new understanding of entrepreneurial intention from a gender perspective. Similarly, the results offer first-hand evidence to inform university students’ career choices.